2017
DOI: 10.3389/fpsyg.2017.01473
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Verbal Instruction and Visual Guidance in Training Pattern Recognition

Abstract: We used a novel approach to examine whether it is possible to improve the perceptual–cognitive skill of pattern recognition using a video-based training intervention. Moreover, we investigated whether any improvements in pattern recognition transfer to an improved ability to make anticipation judgments. Finally, we compared the relative effectiveness of verbal and visual guidance interventions compared to a group that merely viewed the same sequences without any intervention and a control group that only compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…Moreover, researchers and practitioners must be aware that the limiting factor might not be an inappropriate visual search (i.e., gaze behavior) but rather the inability to use the visual information (i.e., perception) (Abernethy, 1990). Recent gaze-intervention studies showed that when training novices with expert-like gaze behavior to improve decision making in a handball-penalty task (Abernethy, Schorer, Jackson, & Hagemann, 2012), or in beach-volleyballdefense (Klostermann, Vater, Kredel, & Hossner, 2015), as well as in pattern recognition in soccer (North, Hope, & Williams, 2017) does not provide any advantage when compared to active control and placebo groups, respectively. It should be noted, however, that different results were obtained when applying gaze trainings in tasks which require to anchor gaze at one location (as for example in basketball free-throw shots, Vine & Wilson, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, researchers and practitioners must be aware that the limiting factor might not be an inappropriate visual search (i.e., gaze behavior) but rather the inability to use the visual information (i.e., perception) (Abernethy, 1990). Recent gaze-intervention studies showed that when training novices with expert-like gaze behavior to improve decision making in a handball-penalty task (Abernethy, Schorer, Jackson, & Hagemann, 2012), or in beach-volleyballdefense (Klostermann, Vater, Kredel, & Hossner, 2015), as well as in pattern recognition in soccer (North, Hope, & Williams, 2017) does not provide any advantage when compared to active control and placebo groups, respectively. It should be noted, however, that different results were obtained when applying gaze trainings in tasks which require to anchor gaze at one location (as for example in basketball free-throw shots, Vine & Wilson, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The mean for the “pattern recognition” category was 2.198 (meaning answers leaning more towards strongly agree) which means students rate themselves fairly when it comes to identifying the pattern of a problem, as presented by previous study one way to enhance the students pattern recognition is to use visual and verbal guidance in approaching a problem rather than merely viewing the sequence, in other terms by letting the students be face to face with the problem rather than simply reading it. [13]…”
Section: Discussionmentioning
confidence: 99%
“…The mean for the "pattern recognition" category was 2.198 (meaning answers leaning more towards strongly agree) which means students rate themselves fairly when it comes to identifying the pattern of a problem, as presented by previous study one way to enhance the students pattern recognition is to use visual and verbal guidance in approaching a problem rather than merely viewing the sequence, in other terms by letting the students be face to face with the problem rather than simply reading it. [13] The mean for the "Application of general strategies for problem solving" category was 2.158 (meaning answers leaning more towards strongly agree), it had the mean that was closest to the (strongly agree) which means students rate themselves the highest (compared to the two other categories) when it comes to their ability of applying what they learnt in dealing with a problem, to enhance this ability even more as proposed by one study is to follow a problem based learning curricula rather than the conventional one, the study found that students in the problem based learning curricula produced extensive elaborations using relevant biomedical information, which was relatively absent from the conventional curricula students. [14] The independent sample T-test results for the "Knowledge of discipline" category showed that the only item for this category (KOD) "I easily remember concepts that I learned long ago" had a mean for females of 3.137 (leaning more towards strongly disagree than males) and a mean for males of 2.778 (more leaning towards strongly agree than females) with a p value of 0.030>0.05 which means there is a statistical significance between males and female when it comes to assessing their knowledge as we can see that males assess themselves in remembering concepts as better than their female counterparts, this however contraindicates other studies, as mentioned before knowledge relies greatly on memory and a study found that when it comes to memory females tend to outperform their male counterparts.…”
Section: Application Of General Strategies For Problem Solving (Ags1)...mentioning
confidence: 99%
“…The ball and the ball carrier are important visual cues that soccer players must focus on to anticipate the outcome of a game situation [ 24 ]. North and colleagues (2017) observed that soccer players were more accurate in recognizing familiar soccer situations presented in point light displays when the ball was present than when it was not [ 53 ]. In situations with soccer-specific trajectories, the presence of the ball would probably have helped to perceive structured collective behaviors and thus the visual tracking of several players.…”
Section: Discussionmentioning
confidence: 99%